Best Practices for Debugging Embedded Software - Shankar, Sanjeev (European Journal of Computer Science and Information Technology, 2025)
This article explores effective debugging strategies for embedded systems that operate under hardware constraints, real-time requirements, and limited visibility. It begins by emphasizing the importance of understanding system fundamentals, including microcontroller architecture, memory layouts, interrupt structures, and communication protocols. The work presents systematic debugging approaches centered on problem reproduction, component isolation, and regression testing, alongside an examination of hardware-based debugging tools such as JTAG/SWD interfaces, in-circuit emulators, oscilloscopes, and logic analyzers. Software-based techniques, including strategic serial output methods and state monitoring mechanisms, are discussed as accessible debugging approaches. The article further explores runtime analysis techniques for memory and resource management before delving into advanced strategies including instrumentation, watchdog mechanisms, and hardware abstraction. Case-specific approaches addressing power issues, communication protocols, and environmental factors complete this comprehensive examination of embedded system debugging methodologies.